Analisis Kebijakan Penanganan Tindak Pidana di Bidang Perpajakan Oleh Direktorat Jendral Pajak - Sembiring, Destiana (UNES Law Review, 2024)
In tax law, apart from administrative sanctions, there are criminal sanctions imposed for violations and crimes. Criminal law as stated in the Criminal Code and those outside it, namely in special provisions (lex specialist). The research method used is literature study, while the data analysis method uses qualitative analysis methods. From the results of the analysis carried out on the focus of this research, the criminal law policy strategy in the field of taxation in the future should be in line with the principle in tax crime, that criminal sanctions in taxation are Ultimum Remidium, meaning that in enforcing violations of tax law the priority is administrative sanctions, while the application of criminal sanctions is carried out if the methods used are no longer effective in making taxpayers comply with tax regulations but can disrupt aspects of legal justice for taxpayers and at the same time the legal rights of taxpayers (society) as a whole. The regulation of the authority of PPNS investigators in investigating criminal acts in the field of taxation is monopolistic, the implementation of investigations carried out by the PPNS Regional Office of the Directorate General of Taxes on taxpayers who commit criminal acts in the field of taxation is in accordance with the rules of the Criminal Procedure Code and the KUP Law, as well as the Regional Office of the Directorate General of Taxes in conducting investigations of taxpayers who commit criminal acts in the field of taxation.